A survey of extracorporeal photopheresis treatment in pediatric patients in the United Kingdom. Issue 1 (13th July 2020) - Flinn, Aisling M.; Macheka, Sheba; Slatter, Mary; Ewins, Anna‐Maria; Gibson, Brenda; Lawson, Sarah; Tailby, Anna; Lucchini, Giovanna; New, Helen; James, Beki; Alfred, Arun; Scarisbrick, Julia; et al.
Abstract: Extracorporeal photopheresis (ECP) is a second‐line therapy in acute and chronic GVHD and solid organ transplant rejection. We report ECP use in 98 pediatric patients in seven UK centers from 2010 to 2017, the majority treated for aGVHD (73.5%). ECP was safe and well tolerated including in low body weight patients. Most patients were on multiple immunosuppressive therapies prior to ECP; 45.9% were able to reduce or stop immunosuppression with treatment. Complete or partial response was reported in almost 60%. This study supports the need to include ECP treatment data to national transplant databases to provide accurate information regarding service provision, patient outcomes, and safety.